Karalność usiłowania w polskim prawie karnym w świetle koncepcji trafu prawnego - Brzozowski, Szymon (Studia Prawa Publicznego, 2026)
The article analyses the benefits and challenges arising from the application of the concept of ‘legal luck’ in the field of criminal attempts. This concept, developed within the philosophy of law, differentiates criminal liability based on factors beyond the perpetrator’s control. The intuition, reflected in judicial practice, that a perpetrator of an attempt should be punished less severely than one of a corresponding completed offence is contested by the fact that the failure to complete most likely results from external factors. An attempt, on the other hand, does not differ at all from the completed offence in terms of the offender’s moral culpability in intending to commit the crime. The article characterises the functions of criminal law and the factors that justify the punishability of attempts. It also outlines the relationship between the criminal law and the moral norms prevailing in a given society. These considerations are juxtaposed with the provisions of the Polish Criminal Code regarding the punishability of attempts, which allows for an assessment of whether the problem of legal luck sheds new light on the shape of the current regulations. The concluding remarks highlight the open-ended character of the statutory regulation of the punishability of attempts in relation to the discussed issue. Accordingly, attention is drawn to the crucial role of judicial awareness of the meaning and role of such punishment for criminal attempts within the axiological system of the society.